ENERGY ABSORPTION CHARACTERISTIC OF BIOMIMETIC BAMBOO THIN⁃WALLED TUBE STRUCTURE FOR CAR CRASH BARRIERS - ZHANG HaiYan; ZHOU GuoHua (Jixie qiangdu)
Based on the macroscopic and microscopic structural characteristics of bamboo,two bionic bamboo structures were proposed:a thin⁃walled tube with variable wall thickness with reinforcing joints(Tube⁃a)and a thin⁃walled bamboo⁃like tube with ribs in a double circle(Tube⁃b).The energy absorption characteristics of the bionic structures under three⁃point bending loading were investigated with the help of Abaqus tool,and the conventional circular tube structure was introduced for comparative analysis.The results show that Tube⁃b has the best performance,its peak crushing force is reduced by about 18.396%compared with the circular tube structure,and its specific energy absorption and energy absorption efficiency are improved respectively by about 50.8%and 38.797%.To further investigate the energy absorption characteristics of the bamboo⁃like structure,the effects of parameters such as loading angle,wall thickness propertyαand cross⁃section propertyβon the energy absorption characteristics of Tube⁃b were explored.It is found that the comprehensive performance of Tube⁃b is better under 0°~20°loading;the energy absorption efficiency of Tube⁃b can be improved appropriately by adjusting the wall thickness property,and the specific energy absorption of Tube⁃b can be improved appropriately by adjusting the cross⁃section property.This study can provide some references for the design of improving the energy absorption characteristics of thin⁃walled structures.